2016
DOI: 10.1002/jmri.25369
|View full text |Cite
|
Sign up to set email alerts
|

Imaging review of hepatocellular carcinoma after thermal ablation: The good, the bad, and the ugly

Abstract: Image-guided thermal ablation is a well-established locoregional technique for the treatment of hepatocellular carcinoma (HCC). HCC surveillance programs have led to an increase in the number of patients diagnosed at an early stage of the disease who are eligible for thermal ablation. Tumor response is assessed on imaging and requires extensive follow-up; thus, radiologists play a key role in defining the technical success and efficacy of treatment as well as identifying progressive disease. Although they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 118 publications
(148 reference statements)
1
8
0
1
Order By: Relevance
“…This result suggested that the tumor characteristics play a key role in the prognosis of patients, which was consistent with previous studies [24,25]. At present, imaging technologies like CEUS, CT and MRI are most commonly used to evaluate the technical effectiveness of MWA [26]. However, it is difficult to detect a microscopic non-necrotic residual disease by these imaging, the tumor residual will lead to early recurrence or local progression.…”
Section: Discussionsupporting
confidence: 88%
“…This result suggested that the tumor characteristics play a key role in the prognosis of patients, which was consistent with previous studies [24,25]. At present, imaging technologies like CEUS, CT and MRI are most commonly used to evaluate the technical effectiveness of MWA [26]. However, it is difficult to detect a microscopic non-necrotic residual disease by these imaging, the tumor residual will lead to early recurrence or local progression.…”
Section: Discussionsupporting
confidence: 88%
“…Biopsies and retreatment should be proposed early to these patients with a high risk of early local recurrence. In the future, low ADC will most likely become an additional argument for close follow‐up and repeat biopsy and retreatment if imaging features change …”
Section: Discussionmentioning
confidence: 99%
“…In the future, low ADC will most likely become an additional argument for close follow-up and repeat biopsy and retreatment if imaging features change. 30 The evolution of the signal intensity of hepatic tumors after RFA is related to the presence of coagulation necrosis and hemorrhage, which is responsible for increased signal intensity on T 1 -and T 2 -weighted images up to 12 weeks after RFA. 31 Consequently, the post-RFA scar has no specific presentation on morphologic MR images with regard to the presence or absence of persistent or local recurring disease.…”
Section: Discussionmentioning
confidence: 99%
“…Des ajustements du rythme de surveillance ont pu être réalisés en cas de doute sur une progression tumorale locale ou à distance. Si une progression était équivoque, d'autres modalités d'imagerie ont été réalisées (échographie avec injection intra veineuse de produit de contraste, IRM avec injection intra veineuse de produit de contraste hépato-spécifique) afin d'obtenir un diagnostic de certitude, en accord avec les stratégies diagnostiques locales, détaillées dans la revue d'imagerie post ablation du CHC jointe en annexe 1 (53). Si l'imagerie ne permettait pas de conclure, une biopsie était réalisée.…”
Section: Suivi Des Patients Et Données De Survieunclassified